Experimental Study on Mechanical Properties of Prefabricated Single-Cracked Red Sandstone under Uniaxial Compression. (29th November 2020) - Yuan, Yue; Fu, Jinlei; Wang, Xiaolei; Shang, Xi
Abstract : This paper aims at the phenomenon of the fractured rock column in underground engineering which is prone to collapse when subjected to ground pressure. Uniaxial compression test and particle flow code (PFC2D) are used to analyze the influence of crack dip angle on the mechanical properties, crack propagation, and the failure mode of red sandstone. From the results, it is observed that the stress–strain curve of the precracked red sandstone can be divided into five stages, and there is a critical stress value in the stage of accelerated crack propagation and unstable fracture of the rock sample. Further, the peak strength, maximum strain, and the elastic modulus of the precracked red sandstone increase with the increase of crack dip angle, and the ultimate failure mode of rock sample changes from the "ladder" type failure to slope uneven failure. Furthermore, from PFC2D simulation, it is found that the tensile microcracks contribute more towards the failure of rock samples than the shear cracks. The contact force chain is very weak at the places where the precracks and macroshear planes are formed. This indicates that the original contact force is weakened due to particle fracture. Therefore, the bearing capacity of the precracked rock samples decreases with the increase in load. From the simulation results, it is found that the displacement at the shear plane of the rock sample is large, and the shear dilatation occurs. With the increase in load, the specimen falls off and is ejected. This is due to the weakening of the contact force between the internal particles. Thereafter, it fractures to produce microcracks, which gradually converge, thus providing a prerequisite for the transformation of elastic strain energy into kinetic energy.